2019
DOI: 10.30798/makuiibf.519599
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Tax Revenues: Panel Data Analysis for Selected Countries

Abstract: için panel veri analiz yöntemiyle araĢtırılmıĢtır. Analizde, potansiyel vergi belirleyicilerinin geliĢmiĢ ve geliĢmekte olan ülkelerdeki vergi performansını etkileyip etkilemediğine dair geliĢtirilen hipotez test edilmiĢ ve serilerin birinci farkta durağan olduğu belirlenmiĢtir. Yapılan analizler neticesinde, veri seti için sabit etkiler modelinin uygun olduğu bulunmuĢtur. Modelin varsayımları sağlayıp sağlamadığı test edilmiĢ ve varsayımlardan sapmalara karĢı geliĢtirilen Driscoll-Kraay dirençli standart tahm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Within the scope of the study, it has been revealed that trade liberalization, another indicator of the globalization phenomenon, has a positive effect on tax revenues. Kutbay (2019) examined 1995-2017 in BRIC+T and G7 countries with panel data techniques to determine the factors effecting tax revenues. As a result of the study, the author argued that a 1% increase in FDIs increased tax revenues by 0.04% in G7 but decreased by 0.03% in BRIC-T countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the scope of the study, it has been revealed that trade liberalization, another indicator of the globalization phenomenon, has a positive effect on tax revenues. Kutbay (2019) examined 1995-2017 in BRIC+T and G7 countries with panel data techniques to determine the factors effecting tax revenues. As a result of the study, the author argued that a 1% increase in FDIs increased tax revenues by 0.04% in G7 but decreased by 0.03% in BRIC-T countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigations that take this causality to another methodology show that the effect of FDI on tax revenues is positive (Gropp & Kostial, 2000;Mahmood & Chaudhary, 2013;Okey, 2013;Balıkçıoğlu, Dalgıç, & Fazlıoğlu, 2016;Pratomo, 2020;Camara, 2022). However, some studies are reporting that the impact of FDIs on tax revenues is negative (Sarısoy & Koç, 2010;Jeza, Hassen, & Ramakrishna, 2016;Bayar & Öztürk, 2018;Kutbay, 2019;Gasparėnienė et al, 2022). Therefore, the effect of FDI on tax revenues is unclear in the empirical literature.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde vergi gelirlerinin ekonomik büyüme, enflasyon oranları ve faiz oranlarının bir fonksiyonu olarak ifade edildiği teorik ve ampirik çok sayıda çalışmaya rastlamak mümkündür Temiz (2008), Gül ve Kenar (2009), Ekici (2009), Göçer ve diğerleri (2010), Mishra (2011), Dackehag ve Hansson (2012), Taha, Loganathan ve Colombage (2012), Muibi ve Sinbo (2013), Velaj ve Prendi (2014), Demir ve Sever (2017), Moźdzıerz (2017), Akbulut (2017), Kutbay (2019).…”
Section: Model Veri Seti Ve Yöntemunclassified